2011
DOI: 10.1371/journal.pone.0018578
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of Decision Rules to Guide Frequency of Monitoring CD4 Cell Count in HIV-1 Infection before Starting Antiretroviral Therapy

Abstract: BackgroundAlthough CD4 cell count monitoring is used to decide when to start antiretroviral therapy in patients with HIV-1 infection, there are no evidence-based recommendations regarding its optimal frequency. It is common practice to monitor every 3 to 6 months, often coupled with viral load monitoring. We developed rules to guide frequency of CD4 cell count monitoring in HIV infection before starting antiretroviral therapy, which we validated retrospectively in patients from the Swiss HIV Cohort Study.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…For all three thresholds considered, decreasing the frequency to 12-monthly led to a potentially unacceptable increase in the proportion starting ART very late (e.g., 11.5% for the 350 threshold), consistent with a study which suggested 12-monthly monitoring only at very high counts (e.g. > 900 cells/ μ l when using the 350 threshold) [16]. For the 200 and 350 thresholds, if the proportion starting very late with 6-monthly monitoring is considered too high, our results for adaptive algorithms involving 6-monthly and then 3- or 4-monthly monitoring after an initial count below 500 cells/ μ l appears to perform about as well as 4- or 3-monthly monitoring throughout with similar or lower monitoring and treatment costs.…”
Section: Discussionsupporting
confidence: 84%
“…For all three thresholds considered, decreasing the frequency to 12-monthly led to a potentially unacceptable increase in the proportion starting ART very late (e.g., 11.5% for the 350 threshold), consistent with a study which suggested 12-monthly monitoring only at very high counts (e.g. > 900 cells/ μ l when using the 350 threshold) [16]. For the 200 and 350 thresholds, if the proportion starting very late with 6-monthly monitoring is considered too high, our results for adaptive algorithms involving 6-monthly and then 3- or 4-monthly monitoring after an initial count below 500 cells/ μ l appears to perform about as well as 4- or 3-monthly monitoring throughout with similar or lower monitoring and treatment costs.…”
Section: Discussionsupporting
confidence: 84%
“…[230][231][232] This research suggests that, in most cases, measurements are carried out too frequently and that most of the change identified is owing to biological (day-to-day) variability and inherent measurement error and therefore not a real change in the health status of the individual. Clinical decisions such as changes to medication titration based on such measurements are potentially detrimental to a patient's health.…”
Section: Discussionmentioning
confidence: 99%
“…More pertinently, statistical models using estimates of mean change and variability in a measurement over time to suggest optimal intervals for monitoring are being developed. A review of four case studies 35 found that for each topic (assessing chol esterol levels for secondary prevention of coronary artery disease, 36 long-term monitoring of blood pressure, 37 measurement of glycated hemoglobin in type 2 diabetes 38 and monitoring of CD4 cell counts in HIV-1 infection 39 ) the results suggested frequent monitoring. There is clear potential for the extension of this work to monitoring in other settings.…”
Section: Discussionmentioning
confidence: 99%
“…Our use of the original Appraisal of Guidelines for Research and Evaluation instrument 39 may be criticized given that it has been 10 years since its publication; however, at the time the framework was chosen, the update to the original instrument 41 and other potentially useful frameworks 42,43 were not yet available. Nevertheless, our approach to assessing the development and content of the guidelines was systematic and provides a reasonable means of comparing guidelines.…”
Section: Strengths and Limitationsmentioning
confidence: 99%